The Impact Of The Technological Radioactive Waste From Romania On The Soils And Crops From The Zones Adjacent To Their Disposal - Gh. Crutu (Society for Mining, Metallurgy & Exploration, 2006)
This paper treats some aspects of the research completed on the impact of the waste generated in the production process of a chemical fertilizer, phosphogypsum, on crops and yields. The article starts with the basic data and the research methods, and continues with details about the research results on the heap waste of phosphogypsum and the soil from its vicinity along with the content in radioactive elements, humus, macro elements and mobile forms of heavy metals. Finally, the absorbtion of radioactive elements from the soil and the uranium concentration in the agricultural cultivations is presented.